2016
DOI: 10.1186/s12909-016-0696-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to success for resident physicians interested in immigrant and refugee health

Abstract: BackgroundCross-cultural care is recognized by the ACGME as an important aspect of US residency training. Resident physicians' preparedness to deliver cross-cultural care has been well studied, while preparedness to provide care specifically to immigrant and refugee populations has not been.MethodsWe administered a survey in October 2013 to 199 residents in Internal Medicine, Pediatrics, and Medicine/Pediatrics at the University of Minnesota, assessing perceived knowledge, attitudes, and experience with immigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
2
30
0
3
Order By: Relevance
“…Underscoring previous research (Alpern, Davey, & Song, 2016), the primary challenge encountered by HPs working with minority patients was the language barrier, which was perceived to contribute to minority groups having significant unmet information needs. This was exacerbated by limited access to culturally appropriate written resources in the patient's own language.…”
Section: Discussionmentioning
confidence: 92%
“…Underscoring previous research (Alpern, Davey, & Song, 2016), the primary challenge encountered by HPs working with minority patients was the language barrier, which was perceived to contribute to minority groups having significant unmet information needs. This was exacerbated by limited access to culturally appropriate written resources in the patient's own language.…”
Section: Discussionmentioning
confidence: 92%
“…Besides, over one-half of the residents feel they are not knowledgeable enough about immigrant and refugee health. 41 Regarding the health coverage of refugees, providers can be totally unaware of the refugee entitlement of care in the reception country, or they may be put in a difficult position where they have to decide whether to provide care or not. 42 A study conducted in Canada to examine the health care providers' knowledge of health care coverage for refugees revealed that the overall level of awareness of refugees' health care coverage is quite low among providers, with around two percent of the study population answering all the questions regarding entitlements correctly.…”
Section: Lack Of Knowledge and Skillsmentioning
confidence: 99%
“…Finally, while adding to their effectiveness as communicators and healers, health workers' greater cultural awareness is correlated with greater satisfaction not only for them but also for the refugee patients in their care. 20,21 The author thanks Katrina Thielman for preparation of the photographs and the entire Marion County Public Health Department refugee health care team for their daily support and dedication. …”
Section: Discussionmentioning
confidence: 99%